The sun is a compass : a 4,000-mile journey into the Alaskan wilds - Van Hemert, Caroline (Little, Brown Spark, 2019)
Documents the biologist adventurer's treks in the vast wilderness region spanning the Pacific rainforest through the Alaskan Arctic, where she and her husband tested their physical boundaries while making profound natural-world connections.